2019
DOI: 10.1172/jci130976
|View full text |Cite
|
Sign up to set email alerts
|

A Clostridia-rich microbiota enhances bile acid excretion in diarrhea-predominant irritable bowel syndrome

Abstract: An excess of fecal bile acids (BAs) is thought to be one of the mechanisms for diarrhea-predominant irritable bowel syndrome (IBS-D). However, the factors causing excessive BA excretion remain incompletely studied. Given the importance of gut microbiota in BA metabolism, we hypothesized that gut dysbiosis might contribute to excessive BA excretion in IBS-D. By performing BA-related metabolic and metagenomic analyses in 290 IBS-D patients and 89 healthy volunteers, we found that 24.5% of IBS-D patients exhibite… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
114
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 134 publications
(138 citation statements)
references
References 74 publications
8
114
0
1
Order By: Relevance
“…Importantly, the authors showed that the BA-positive group, when compared to the BA-negative group, also showed raised serum C4 and total BA levels, with lower FGF19. Total fecal BAs were associated with increased symptom severity, increased BA synthesis and impaired FGF19 feedback, making the Zhao et al study patients representative of those studied previously (16).…”
Section: A Possible Cause Of Primary Bile Acid Diarrheamentioning
confidence: 80%
See 4 more Smart Citations
“…Importantly, the authors showed that the BA-positive group, when compared to the BA-negative group, also showed raised serum C4 and total BA levels, with lower FGF19. Total fecal BAs were associated with increased symptom severity, increased BA synthesis and impaired FGF19 feedback, making the Zhao et al study patients representative of those studied previously (16).…”
Section: A Possible Cause Of Primary Bile Acid Diarrheamentioning
confidence: 80%
“…This group had an increase in their microbiota in Firmicutes, including Clostridia and especially Clostridium scindens, with significantly higher abundance of 7-dehydroxylation/dehydrogenation genes. The abundance of C. scindens was positively associated with total fecal BA and serum C4, and, notably, was inversely related to serum FGF19 levels (16).…”
Section: A Possible Cause Of Primary Bile Acid Diarrheamentioning
confidence: 87%
See 3 more Smart Citations